Malaysia’s development challenges for moving up the value chain: Analysis of cluster development policy. - Kitamura, Kenichi. (Tufts Archival Research Center, 2015)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: In an effort to become a high-income country, Malaysia has been pursuing development of clusters as a key policy for productivity growth since 1990s. However, Malaysia has not moved up the value chain and remains a middle-income country. This paper aims to identify key challenges for Malaysia and analyzes the government policy towards cluster development. In order to examine the nature of clusters, the analysis focuses on electrical and electronics, particularly semiconductors. The electrical and electronics industry, with semiconductor cluster at its core, is the most developed industry in Malaysia in terms of value added, employment, export, and FDI. After analyzing the government policies for cluster development, the paper concludes that further coordination of stakeholders and continuous effort to develop human resource and science and technology over years are keys for Malaysia’s further economic development.